Diseño de un sistema de conversión de energía mecánica a eléctrica a partir de dos máquinas de gimnasio (Elíptica y Bicicleta estática) (2016)
The static bicycle and elliptic are an effective means of fitness. can be used for an electrical energy production, on each machine thought its crank movement A person can produced a considerable amount of mechanical power when performing any type of exercise, that can be realized due to food intake, which provides an amount of energy around 4000 Kcal, whereby the human turned a valuable resource, for by a generator can take this mechanical energy to produce electricity.